Relationship Between Pregnant Women's Knowledge About Pregnancy Nutrition And The Incidence Of Chronic Energy Deficiency (CHD) At The Muara Kati Health Centre In 2024 - Agustinah, Nia; Sari, Liya Lugita; Situmorang, Ronalen (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
Background: Based on data from the World Health Organization (WHO) maternal mortality is still quite high, every day around the world about 808 women die from complications in pregnancy or childbirth. The prevalence of SEA among pregnant women in the world reaches 41%. Data in Asia the proportion of pregnant women with SEZ is around 15.3%, Thanzania shows as many as 19% of pregnant women experience SEZ (WHO, Maternal mortality, 2019). Research Objective: This is to determine the relationship between the level of nutritional knowledge in pregnant women with the incidence of SEZ in the Muara Kati Health Centre working area in 2024. Research Methods: The method used is descriptive research design. Descriptive method is a research method carried out with the main purpose of making a description or descriptive of a situation objectively. (Hidayat, 2022). Data was collected by distributing questionnaires to 44 respondents who were pregnant at Muara Kati Health Centre. Research Results: Research results A total of 15.9% of pregnant women who experience the incidence of SEZ. The results of bivariate test analysis there is a relationship between knowledge and the incidence of SEZ in pregnant women where the results of the chi-square test with interpretation obtained p-value = .000> 0.05. Suggestion: Researchers suggest that the muara kati health centre is expected to provide information on the relationship between knowledge of pregnant women about nutrition with the incidence of pregnancy SEZ and can be used as a supporting material for program planning and prevention of SEZ in pregnant women and evaluating existing programs.